그룹코칭 프로그램이 항암화학요법을 받는 유방암 환자의 우울, 불안, 희망에 미치는 효과 - 성소령(Seong, So Ryoung); 조문경(Cho, Moon-kyung); 김지윤(Kim, Jeeyoon); 김여옥(Kim, Yeo Ok) (Asian oncology nursing, 2017)
Purpose: The purpose of this study was to examine the effect of a group coaching program (GCP) on depression, anxiety, and hope in women breast cancer patients undergoing chemotherapy. Methods: A total of 152 patients were enrolled and randomly assigned to an experimental group receiving the GCP (N=76) and an untreated control group (N=76). Data collection consisted of three measurements of depression, anxiety, and hope (pre, post, and 3weeks later). The intervention was a one-time GCP consisting of 5 subparts for 30-40 minutes for a group of 3-4 people, conducted by a single nurse. Results: The scores of depression, anxiety, and hope changed significantly over time (p<.001, p<.001, p<.001). Depression, anxiety, and hope changes were significantly different between the experimental and control groups (p<.001, p<.001, p<.001). There was a difference in depression, anxiety, and hope among the groups according to the implementation of the GCP (p<.001, p<.001, p<.001). In the experimental group, depression, anxiety, and hope level were significantly different between the pre- and post-test (p<.001), pre- and 3weeks later-test (p<.001), but not in the control group. Conclusion: The GCP for women breast cancer patients receiving chemotherapy was effective in reducing depression and anxiety, and increasing hope. KCI Citation Count: 1